A co-operative protection strategy to synthesize highly active and durable Fe/N co–doped carbon towards oxygen reduction reaction in Zn–air batteries. (September 2021) - Xu, Chenxi; Chen, Liang; Wen, Yongliang; Qin, Shifeng; Li, Huanxin; Hou, Zhaohui; Huang, Zhongyuan; Zhou, Haihui; Kuang, Yafei
Abstract: As promising alternatives to noble metal catalysts such as platinum-based electrocatalysts, Fe/N co–doped carbon (Fe–N–C) materials attract extensive attention because of their high activity and good durability. It is acknowledged that non–crystalline Fe–Nx moieties and crystalline iron–based nanoparticles as important active sites, largely determine the catalytic performance of Fe–N–C catalysts. However, the design and preparation of Fe–N–C catalyst still suffer from insufficient effective active sites because of the inevitable agglomeration phenomenon. In our work, from the perspective of minimizing catalyst size and prohibiting catalyst agglomeration, we put forward a co-operative protection strategy and successfully fabricate abundant Fe–Nx moieties and highly dispersed hyperfine Fe3 C nanodots jointly decorated N–doped carbon framework (Fe–Nx /Fe3 C@NC). By systematic characterization and analysis, we find the formation of these abundant active sites (Fe–Nx moieties and Fe3 C nanodots) originates from the co-operative protection of different components in original precursors. As a result, the obtained product, Fe3 C/Fe–Nx @NC hybrid displays high activity and robust durability towards oxygen reduction reaction (ORR) in both alkaline and acid medium. When employed as the cathode catalyst for Zn–air batteries, Fe3 C/Fe–Nx @NC also exhibits comparable performance to that of commercial Pt/C catalyst. Clearly, our adopted strategy provides a good guidance on the preparation of high–performance transition metal–N–C–based catalysts for energy storage and conversion systems. Graphical abstract: A co-operative protection strategy is developed to prepare Fe–Nx /Fe3 C@NC with abundant Fe–Nx moieties and well–distributed hyperfine Fe3 C nanoparticles. Image 1 Highlights: A co-operative protection strategy was used to prepare Fe–Nx moieties and highly dispersed hyperfine iron carbide (Fe3 C) nanodots jointly decorated N–doped carbon framework (Fe–Nx /Fe3 C@NC). Fe–Nx /Fe3 C@NC possesses abundant Fe–Nx moieties and hyperfine Fe3 C nanodots. Fe3 C/Fe–Nx @NC shows excellent oxygen reduction reaction (ORR) performance in Zinc (Zn)–air batteries.